The Effects of Milk Consumption on Blood Calcium Concentration and Bone Density of Adolescents Boys - Suryono, Suryono; Setiawan, Budi (Department of Technology of Agricultural product (THP) Jambi University, 2021)
Milk consumption during adolescence is considered an early means of preventing osteoporosis in adults. Osteoporosis is a systemic skeletal disease characterised by low bone density and microarchitectural deterioration of bone tissues, with a consequent increase in bone fragility and suspectibility to fracture. Augmenting bone mass during adolescence has been suggested as a strategy to prevent osteoporosis, because adolescents may represent the final opportunity for substantially increasing bone mass before skeletal consolidation. The purpose of this study was to determine effects of fresh and high calcium milk on blood calcium concentration and bone density. Variables measured in this study were blood calcium concentration, bone density of spine and bone density of whole body. The study using 55 adolescent boys that had 17 to 19 years old. The design of this study is nested randomized design with two factors are kind of mil (fresh milk, high calcium milk) and volume of each kind of milk (250 ml, 500 ml, 750 ml). Results of the study indicated that fresh and high calcium milk in this research not significant effects (P>0.05) on blood calcium concentration and bone density of whole body. But, high calcium milk consumption was able to increase bone density. It was found that high calcium consumption showed very highly significant effect (P<0.01) on bone density of spine with 1.79% contributions. Based on general linear model equation, bone density of trunk can be estimated by high calcium milk consumption. Keywords : milk consumption, adolescence, blood calcium concentration, bone density